Pembinaan Karakter Religius pada Peserta Didik di MIN 10 Kota Banda Aceh - Al Mukhlisin, Muhammad Alief; Idris, Saifullah; Fikri, Mumtazul (Jurnal Ilmiah Guru Madrasah, 2025)
This study aims to analyze the forms of religious character, development strategies, and the obstacles and solutions in the internalization of religious values among students at MIN 10 Kota Banda Aceh. A qualitative descriptive approach was employed, with data collected through participant observation, in-depth interviews, and documentation. The participants included the principal, teachers, and students selected through purposive sampling. Data analysis followed the Miles, Huberman, and Saldaña interactive model. The findings indicate that students’ religious character is reflected in habitual worship, respectful behavior, and social empathy. Character development is implemented through five main strategies: role modeling, spiritual storytelling, religious advice, habituation of religious practices, and thematic discussions, supported by QURMA programs and extended diniyah hours. Major challenges include limited human resources, time constraints, funding, and inconsistent family support. These challenges are addressed through managerial innovations, stakeholder collaboration, and strengthened communication. This study recommends a collaborative and culturally grounded model of religious character education for Islamic elementary schools. Abstrak Penelitian ini bertujuan untuk menganalisis bentuk karakter religius, strategi pembinaan, serta hambatan dan solusi dalam proses internalisasi nilai-nilai religius pada peserta didik di MIN 10 Kota Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi partisipatif, wawancara mendalam, dan dokumentasi. Subjek penelitian terdiri atas kepala madrasah, guru, dan siswa yang dipilih secara purposive. Analisis data dilakukan dengan model Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa karakter religius peserta didik terwujud melalui kebiasaan ibadah, sikap sopan santun, dan kepedulian sosial. Pembinaan dilakukan melalui lima strategi utama: keteladanan, kisah spiritual, nasihat agama, pembiasaan praktik keagamaan, dan diskusi tematik, yang diperkuat oleh program QURMA dan tambahan jam diniyah. Hambatan utama mencakup keterbatasan sumber daya manusia, waktu, dana, serta variasi dukungan keluarga. Namun, hambatan tersebut dapat diatasi melalui inovasi manajerial, sinergi antar pemangku kepentingan, dan penguatan komunikasi. Penelitian ini merekomendasikan model pembinaan karakter religius berbasis kolaboratif dan kearifan lokal untuk madrasah ibtidaiyah.